Control of Subduction Zone Age and Size on Flat Slab Subduction - Schellart, Wouter Pieter (Frontiers in Earth Science, 2020)
Flat slab subduction is an enigmatic style of subduction where the slab attains a horizontal orientation for up to several hundred kilometers below the base of the overriding plate. It has been linked to the subduction of buoyant aseismic ridges or plateaus, but the spatial correlation is problematic, as there are subducting aseismic ridges and plateaus that do not produce a flat slab, most notably in the Western Pacific, and there are flat slabs without an aseismic ridge or plateau. In this paper an alternative hypothesis is investigated which poses that flat slab subduction is associated with subduction zones that are both old (active for a long time) and wide (large trench-parallel extent). A global subduction zone compilation is presented showing that flat slabs preferentially occur at old (> ~80-100 Myr) and wide (≥ ~6000 km) subduction zones. This is explained by the tendency for wide subduction zones to decrease their dip angle in the uppermost mantle with progressive time, especially in the center. A set of numerical subduction models confirms this behavior, showing that only the central parts of wide slabs progressively reduce their slab dip, such that slab flattening, and ultimately flat slab subduction, can occur. The models further show that a progressive decrease in slab dip angle for wide slabs leads to increased vertical deviatoric tensional stresses at the top surface of the slab (mantle wedge suction), facilitating flat slab subduction, while narrow slabs retain steep dip angles and low vertical deviatoric tensional stresses. The results provide a potential explanation why present-day flat slabs only occur in the Eastern Pacific, as only here subduction zones were old and wide enough to initiate flat slab subduction, and why Laramide flat slab subduction and South China flat slab subduction were possible in the geological past.